Long-Term Results of the Diagnostic Tests for Subacromial Impingement Syndrome - Bayram Kelle; Ferdi Yavuz; Burcak Akin (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: Subacromial impingement syndrome (SIS) is the most common cause of shoulder pain. Specific tests and imaging methods are important for the diagnosis. The aim of this study was to evaluate the long term results of specific tests after the treatment. Material and Methods: Eighty-six patients with SIS were enrolled in this study. These patients were divided into two groups as local steroid injection (group I) and conventional physical therapy (groupII). Hawkins-Kennedy, Neer and Jobe tests were applied to patients in both groups before treatment. The tests were classified according the declaration of patients as positive, suspect positive and negative. The tests were applied after treatment again. Results: There were no significant differences for demographic data between groups. The all tests in both group were found mostly positive. It was seen significant change at the third months after treatment. Conclusions: The specific tests were important fort he diagnosis of SIS, furthermore they can demonstrate the efficacy of treatments. The combinad application of these tests are more important for the diagnosis and follow-up of SIS. [Cukurova Med J 2015; 40(4.000): 794-799]